Factors Influencing Multicultural Team effectiveness in Nepalese Financial Institutions of Kathmandu Valley - Sedhai, Gopal Prasad; Singh, Gobind Kumar; Thapa, Shweta (International Journal of Multidisciplinary Approach Research and Science, 2025)
The effective management of multicultural teams is crucial for fostering a harmonious and productive work environment in Nepalese financial institutions, particularly within the Kathmandu Valley. This study investigates the dimensions influencing multicultural team effectiveness, including working environment, communication quality, superior’s support, remuneration, and cultural intelligence. Employing descriptive and causal comparative research designs, the study utilized convenience sampling to gather primary data from 418 respondents across 17 commercial banks. A structured questionnaire was administered, and Cronbach's alpha was employed to assess reliability. The analysis revealed that working environment, communication quality, superior's support, and cultural intelligence has positive and significant impact on multicultural team effectiveness. However, remuneration has negative and insignificant influence on the multicultural team effectiveness. The study concludes that improvements in working environment, communication quality, superior’s support, remuneration, and cultural intelligence were associated with enhanced team performance. The findings highlight the necessity for financial institutions to implement strategies that promote effective management of multicultural teams. Recommendations include providing meditation sessions to alleviate work-related stress, fostering an inclusive culture through team-building activities, and offering training on cultural sensitivity and communication styles. This research adds to the existing literature by providing empirical evidence on the factors influencing multicultural team effectiveness in Nepalese financial institutions and outlining practical management strategies.